2018
DOI: 10.1002/pc.25057
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration of size and temperature‐dependent carbon nanotube (CNT)‐reinforced composite nanoplates with CNT agglomeration

Abstract: Free vibration analysis of size‐dependent carbon nanotube‐reinforced composite (CNTRC) nanoplates, resting on the visco‐Pasternak foundation is studied. The Mori–Tanaka approach, considering carbon nanotube (CNT) agglomeration, is employed to derive the material properties of the composite nanoplates. The analysis is carried out for the uniform distribution (UD) and randomly oriented (RO) distribution of single‐walled carbon nanotubes (SWCNTs) while the nanoplate and the foundation are considered to be tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 91 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…With this study, it was concluded that the presence of the foundation beneath the nanoplates reduced the effects of CNT agglomeration. The same author led another study on the dynamic behaviour of size-and temperature-dependent agglomerated CNTRC nanoplates resting on a visco-Pasternak foundation [19], where it was concluded that ignoring the agglomeration effect causes an overestimation of the elastic properties and the presence of the Pasternak foundation clearly increased the nanoplate natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…With this study, it was concluded that the presence of the foundation beneath the nanoplates reduced the effects of CNT agglomeration. The same author led another study on the dynamic behaviour of size-and temperature-dependent agglomerated CNTRC nanoplates resting on a visco-Pasternak foundation [19], where it was concluded that ignoring the agglomeration effect causes an overestimation of the elastic properties and the presence of the Pasternak foundation clearly increased the nanoplate natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical conductivity in polymer nanocomposites containing conductive nanofiller such as carbon nanotubes (CNT) provides some applications in electronics, shielding, actuating, and sensing . The conductivity of nanocomposites meaningfully improves at a critical concentration as percolation threshold, because the number of nanoparticles at this point is enough to establish the conductive networks .…”
Section: Introductionmentioning
confidence: 99%
“…30 Micro-and nano-powder fillers are mostly used to enhance hardness, elastic moduli, impact, wear, and thermal resistance, while reducing cost and mechanical shrinkage. 14 For example, micron-sized rigid glassy spheres, elastic rubber particles, rigid nano-sized CaCO 3 , 31 Al 2 O 3 , 32 SiO 2 , 33 and TiO 2 34 powders, carbon nano-tubes, [35][36][37] and nano-clay (NC) platelets 38 have been used as reinforcements.…”
Section: Introductionmentioning
confidence: 99%